2020
DOI: 10.1016/j.cub.2020.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Bacterial Genomes Reveal a High Diversity of Treponema pallidum Strains in Early Modern Europe

Abstract: Highlights d Four ancient Treponema pallidum genomes from early modern Europe were reconstructed d The genomes are highly diverse and include syphilis, yaws, and an unknown lineage d The new ancient T. pallidum lineage is a basal sister group to yaws and bejel d Molecular clock dating would allow a pre-Columbian origin of T. pallidum in Europe

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
87
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 135 publications
(241 reference statements)
15
87
1
Order By: Relevance
“…We showed that TPE genomes in Maryland County form a monophyletic clade that is clearly distinct from other publicly available TPE genomes. The low genomic diversity within samples from Liberia is consistent with previous observations regarding low mutation rates of TPE and TPA (14,23) yet contrasts the genetic and geographic structuring observed in the broader global phylogeny. This finding suggests evolution and expansion of local TPE strains from a common ancestor subsequent to the benzathine penicillin-based eradication campaigns conducted until the 1960s, rather than recent importation from elsewhere.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We showed that TPE genomes in Maryland County form a monophyletic clade that is clearly distinct from other publicly available TPE genomes. The low genomic diversity within samples from Liberia is consistent with previous observations regarding low mutation rates of TPE and TPA (14,23) yet contrasts the genetic and geographic structuring observed in the broader global phylogeny. This finding suggests evolution and expansion of local TPE strains from a common ancestor subsequent to the benzathine penicillin-based eradication campaigns conducted until the 1960s, rather than recent importation from elsewhere.…”
Section: Discussionsupporting
confidence: 88%
“…Ancestral reconstruction on the phylogeny inferred that the maximum number of substitutions from the common ancestor of all genomes sequenced from Maryland County was 4. Contextualized by previous estimates that the molecular clock rate of T. pallidum is 4-9 years/substitutions/genome (14,23), which suggests a recent common ancestor within the past 16-36 years. Despite low overall diversity, there remained evidence of local geographic separation within Maryland County genomes, particularly among 2 northernmost communities ( Figure 3, clusters A, B).…”
Section: Reidentification Of Yaws Liberiamentioning
confidence: 92%
“…We excluded 8 samples from strains known to be heavily passaged or with uncertain collection dates from the previous dataset of 528, giving a dataset of 520 samples and 883 variable sites. We inferred a median molecular clock rate of 1.28 ×10 −7 substitutions/site/year (95% Highest Posterior Density (HPD) 1.07 ×10 −7 – 1.48 ×10 −7 ), equivalent to one substitution/genome every 6.9 years, consistent with recent analyses 4,6 .…”
Section: Resultssupporting
confidence: 83%
“…This filtered dataset comprised 401 new and 127 published genomes (Supplementary Data 1), but excluded the only sample from Belgium, leaving 22 countries in the analysis. After excluding 19 regions of recombination and genomic uncertainty due to gene orthology or repetitive regions 3,4,6 , we used Gubbins 26 to infer a further 19 regions of putative recombination (see Methods and Supplementary Data 2 for details). We refer to the resulting masked sequence alignment as the core genome and used it to infer a whole genome maximum likelihood phylogeny using IQ-Tree 27 (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation